Effects of various insecticides on ragweed leaf beetle (Ophraella communa LeSage) - Tamaš, Nenad; Sretenović, Marko; Miletić, Novica (Acta herbologica, 2022)
In a laboratory screening test, the effects of acetamiprid, lambda-cyhalothrin, abamectin, phosmet and chlorantraniliprole on ragweed leaf beetle (Ophraella communa LeSage) were examined in order to investigate their selectivity for this species in crops and orchards where they are used, but also the possibility of their application in case of its appearance on cultivated sunflower in order to prevent damage. Commercial insecticidal formulations were used for the test, in doses recommended for the control of a related species, Colorado potato beetle. The experiment was performed according to a standard, partially adapted method for determining the sensitivity of the Colorado potato beetle to insecticides.Based on the test results, it was determined that lambda-cyhalothrin, abamectin and phosmet are non-selective for this species, causing high mortality of individuals (100%). Weaker effects (mortality of 88.16% -89.39%) were shown by acetamiprid, and its effect on this insect species can be assessed as weakly selective. Chlorantraniliprol showed high selectivity and very poor efficacy in O. communa control (mortality of 40.79% -45.45%). Its application in crops and orchards would not significantly reduce the number of ragweed leaf beetles.
Keywords: O. communa, insecticides, effects